2020
DOI: 10.24926/jcotr.v27i1.2334
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Social Expectations of Incoming College Students

Abstract: Students’ beliefs about themselves and their abilities shape their first-semester college experience. Previous studies have connected growth mindset and grit with increased graduation and retention relates, but mindset is likely to relate to other factors besides academic performance and re-enrollment. This article examines incoming students’ beliefs about their intelligence, social skills, work habits, and effort. Students (N = 332) also rated their likely reactions to a variety of hypothetical academic and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These studies suggest that having a growth mindset can increase academic success and resilience when students are faced with failure. Thus, colleges and universities need to determine how to leverage the knowledge that having a genuine growth mindset—and not a merely a performative growth mindset, which could occur based on the ubiquity of the theory in K‐12 schools (Korstange et al, 2020)—is crucial for academic success, resilience, and authentic belief that one's intelligence is malleable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggest that having a growth mindset can increase academic success and resilience when students are faced with failure. Thus, colleges and universities need to determine how to leverage the knowledge that having a genuine growth mindset—and not a merely a performative growth mindset, which could occur based on the ubiquity of the theory in K‐12 schools (Korstange et al, 2020)—is crucial for academic success, resilience, and authentic belief that one's intelligence is malleable.…”
Section: Discussionmentioning
confidence: 99%
“…Second, educational psychology skills (e.g., self‐regulation and self‐control, holding one's attention in the face of distractions; Moran, 2018) and understanding the differences in growth and fixed mindsets are necessary for students to succeed in college. One of those crucial lessons, especially for first‐year students, is the importance of a growth mindset, especially for those students who do not already have growth‐oriented beliefs (Korstange et al, 2020). As demonstrated in this study, mindsets are malleable, and many different activities can influence an individual's attributions and goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often there is a mismatch between students' beliefs, expectations and the academic and life demands they face. Those who are more collegeready and have a so-called growth mindset show a higher success rate compared to those who have a fixed mindset (Dweck, 2006;Korstange et al, 2020). Members of the earlier group are more successful because they believe that their academic abilities and social skills are changeable and, therefore, look at challenges as opportunities to grow.…”
Section: Transition To Higher Education and Student Retentionmentioning
confidence: 99%
“…The idea of verifying this theory is at the center of the current study, as previous work detailed later, has identified that unintentional actions can influence the behavior of others. These unintentional interactions can also be critical in identifying the perceptions of the collegiate experience as students arrive on campus [5], and in turn, can frame a student's perception of what college is or should be, impacting retention and satisfaction [6].…”
Section: Introductionmentioning
confidence: 99%